The Impact of COVID-19 on Corporations and Corporate Law in Malaysia - Krishnan, Loganathan; Chan, Wai Meng. (Singapore : Springer Nature Singapore : Imprint: Springer, 2022)
This book analyzes the impact of COVID-19 on corporations in Malaysia, discussing the challenges and the corporations' responses to them. The relevant provisions in the Companies Act 2016 are examined, and where necessary, reforms are proposed in light of the new business environment brought on as a result of the pandemic. The book also discusses the interim measures initiated by the various regulators in order to mitigate the impact of COVID-19 and analyzes the adequacy of such measures by drawing analogous positions from countries such as the UK, Australia, and Singapore. This book is a helpful guide for practitioners to manage the impact of COVID-19 on corporations and the Companies Act 2016. The book is a reference point for regulators and policy makers in crafting policies to combat the impact of COVID-19. .
Chapter 1. Introduction -- Chapter 2. Directors' fiduciary duties -- Chapter 3. Directors' duty to exercise due care, skill and diligence -- Chapter 4. Auditors' duties and obligations -- Chapter 5. Board meetings, general meetings and shareholder activism -- Chapter 6. Compliance with statutory requirements -- Chapter 7. The covid-19 and criminal liability risks for corporations -- Chapter 8. Effect on capital markets -- Chapter 9 -- Corporate restructuring and insolvency. .
Keywords: Commercial law; Financial risk management; Accounting; Capital market; Business Law; Risk Management; Financial Accounting; Capital Markets